DEPARTURE TRAJECTORY OPTIMIZATION FOR NOISE ABATEMENT PROCEDURE IN SOEKARNO-HATTA INTERNATIONAL AIRPORT - Suryo, Vincentius N.S.; Grüter, Benedikt; Diepolder, Johannes; Ruseno, Neno; Holzapfel, Florian (BRIN Publishing, 2020)
Air traffic noise emission has been a growing concern for communities living within the vicinity of airports due to a massive increase in air traffic volume in recent years. This work focuses on the noise annoyance problem by optimizing one of the RNAV trajectories, which aims to minimize the noise footprint of a flying aircraft in a low altitude trajectory. Optimal control theory is applied to minimize the number of awakenings caused by a departing aircraft while constraining the relative increase of fuel consumption with regard to a fuel-minimal trajectory. The aircraft simulation model is based on the BADA 3 database, while the noise is modeled according to the ANP database, both published by EUROCONTROL. The methodology is demonstrated for the Soekarno-Hatta International Airport (CGK) in Jakarta; the result shows the comparison between fuel-minimal trajectories and noise-minimal trajectories for seven aircraft types representing the fleet mix at CGK. The number of awakenings of the noise-minimal trajectories is reduced by 30.33%, with an additional of 5% fuel consumption for the seven aircraft types when compared to the fuel-minimal trajectory.